2014
DOI: 10.2485/jhtb.23.93
|View full text |Cite
|
Sign up to set email alerts
|

Zirconia Implants with Laser Surface Treatment: Peri-Implant Bone Response and Enhancement of Osseointegration

Abstract: The aim of this study was to prepare zirconia implants with laser-modified surfaces and to evaluate peri-implant tissue response and osseointegration in an animal study. The experimental zirconia implants received one of the following surface treatments and were placed in the tibiae of SD rats: vertical irradiation with a fiber laser (vertical fiber laser), horizontal irradiation with a fiber laser (horizontal fiber laser), vertical irradiation with a Neodymium-doped yttrium orthovanadate (YVO4) laser (vertica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…We investigated how modifying surface topography affects tissues surrounding zirconia implant bodies (ZrI) inserted in a rat tibia. We have previously tested osseointegration after placement of threaded zirconia implants . In the present study, to avoid the effects of the threads on osseointegration and to link the in vivo evaluation to the in vitro results, cylindrical, machined‐surfaced zirconia ceramics without threads were prepared as controls (S‐ZrI) (Figure A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We investigated how modifying surface topography affects tissues surrounding zirconia implant bodies (ZrI) inserted in a rat tibia. We have previously tested osseointegration after placement of threaded zirconia implants . In the present study, to avoid the effects of the threads on osseointegration and to link the in vivo evaluation to the in vitro results, cylindrical, machined‐surfaced zirconia ceramics without threads were prepared as controls (S‐ZrI) (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…The results of our previous in vivo studies showed the stimulating effect of laser irradiation on osseointegration. 26,27 In the present study, by using implant bodies without a thread, we could assess the effectiveness of only the surface topography created by laser irradiation, and compare the in vivo and in vitro results. The results clearly show that surface roughness of implant bodies created by laser irradiation increased the new bone formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A few surface modifications to zirconia have been reported for the purpose of improving the bone-tissue response. For example, calcium ion incorporation [17], apatite coating [18,19], ultraviolet irradiation (UV) [20][21][22], sand-blasting [15,23,24], acid-etching [25], and laser treatment [26][27][28][29][30] have been postulated for the effective surface treatment of zirconia. A combination of large-grit sandblasting and acid etching was also reported to be a useful method [15,[31][32][33].…”
Section: Introductionmentioning
confidence: 99%